2013
DOI: 10.2528/pier13010105
|View full text |Cite
|
Sign up to set email alerts
|

Brain MR Image Classification Using Multiscale Geometric Analysis of Ripplet

Abstract: Abstract-We propose an automatic and accurate technique for classifying normal and abnormal magnetic resonance (MR) images of human brain. Ripplet transform Type-I (RT), an efficient multiscale geometric analysis (MGA) tool for digital images, is used to represent the salient features of the brain MR images. The dimensionality of the image representative feature vector is reduced by principal component analysis (PCA). A computationally less expensive support vector machine (SVM), called least square-SVM (LS-SV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(88 citation statements)
references
References 21 publications
1
87
0
Order By: Relevance
“…Zhang et al [13] suggested that removing spiderweb-plot yielded the same classification performance. Das et al [14] proposed to use Ripplet transform (RT) + PCA + least square SVM (LS-SVM), and the 5 × 5 CV shows high classification accuracies. Kalbkhani et al [15] modelled the detail coefficients of 2-level DWT by generalized autoregressive conditional heteroscedasticity (GARCH) statistical model, and the parameters of GARCH model are considered as the primary feature vector.…”
Section: Existing Pathological Brain Detection Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang et al [13] suggested that removing spiderweb-plot yielded the same classification performance. Das et al [14] proposed to use Ripplet transform (RT) + PCA + least square SVM (LS-SVM), and the 5 × 5 CV shows high classification accuracies. Kalbkhani et al [15] modelled the detail coefficients of 2-level DWT by generalized autoregressive conditional heteroscedasticity (GARCH) statistical model, and the parameters of GARCH model are considered as the primary feature vector.…”
Section: Existing Pathological Brain Detection Systemsmentioning
confidence: 99%
“…They consist of normal brain images and pathological brain images from seven types of diseases: glioma, meningioma, Alzheimer's disease, Alzheimer's disease plus visual agnosia, Pick's disease, sarcoma, and Huntington's disease. In addition, Das et al [14] proposed a third dataset "Dataset-255", which contains 11 types of diseases, among which 7 types are the same as above, and 4 new diseases (chronic subdural hematoma, cerebral toxoplasmosis, herpes encephalitis, and multiple sclerosis) were included. Figure 2 shows samples of a normal brain and 11 types of diseases.…”
Section: Dataset and CV Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…For a comprehensive comparison of decision models' performance on the multi-classification of brain MRIs, the proposed research compared five different decision models (J48, kNN, RF, and LS-SVM with polynomial (Poly) and radial basis functions (RBF)). For comparative analysis with the proposed system, some of the other published methods from recent literature [6,18,20,21] were also tested using the same large datasets.…”
Section: Introductionmentioning
confidence: 99%
“…Image fusion methods have been proposed by different researcher in literature [2]- [9]. Image fusion techniques divided into unite state as pixel, feature and decision level.…”
Section: Introductionmentioning
confidence: 99%